Potentiel d’élimination des déchets végétaux (feuilles de Mangifera Indica et de Manihot Utilissima) par méthanisation à Kinshasa (République Démocratique du Congo) - Philippe Mambanzulua Ngoma; Serge Hiligsmann; Eric Sumbu Zola; Marc Ongena; Philippe Thonart (VertigO)
In Democratic Republic of Congo, the capital, the city province of Kinshasa produces annually about 2.2 million tons of wastes mainly constituted (66 %) of organic matters containing 94 % are vegetable wastes. Mangifera Indica and Manihot Utilissima leaves are the main components of these wastes. They are generated via the households and the markets but they are not suitably valorized. Some farmers use them like green fertilizer but they do not achieve the expected results. By this fact, these wastes embarrass and pollute the environment with negative consequences on public health. On another point of view, the Kinshasa households meet enormous difficulties to collect enough wood for their energy needs. As a consequence, the anarchical exploitation of wood entails the deterioration of the ecosystems and the public health. These negative impacts on the environment could be reduced sustainably and simultaneously by rational exploitation of bio-energy and bio-fertilizers resulting from the anaerobic digestion or methanization of this vegetable biomass. This energetic potential from methanization of Mangifera Indica and Manihot Utilissima leaves could reduce by 39 % and 134 % the wood consumption in the households respectively. Moreover by land spreading the digestates produced would cover the deforested surface related to the yearly consumption of wood coal. These evaluations show an interesting potential of the vegetable wastes for a cleaner environment, green energy production, reforestation and agriculture. Therefore, these wastes should be sorted out and processed directly in their generation places in order to minimize the costs for transportation and industrial treatment.